Mn-Doped CeO2: DFT+U Study of a Catalyst for Oxidation Reactions - Garcia Pintos, Delfina (2013)
In this work, we performed DFT+U periodic calculations to study the geometric and electronic properties of 12.5% Mn-doped CeO2 solid solution. The doping with Mn allowed some Mn2+ cations to substitute Ce4+ ions into the CeO2 lattice and thus drove the formation of a stable O-deficient bulk fluorite-type structure. The Mn-doped CeO2(1 1 1) surface, generated upon the cleavage of the O-deficient bulk, exhibits Mn cations in a (3+) oxidation state. Spin-polarized energy calculations and charge analysis also evidenced the effect of Mn-dopant in facilitating the creation of surface oxygen vacancies; which reflected in extended surface and subsurface ions relaxation and reduction of Mn atoms located on surface and inner cationic layers. Concerning the oxidation state of Ce, it remained unaltered as Ce4+ when an O atom was removed from the topmost anionic layer of the surface system. Reduction of a Ce4+ cation to Ce3+ was evidenced after the creation of a second surface O-vacancy. Our results indicate facilitated surface oxygen release, Mn3+/Mn2+ redox couples formation, and promoted anionic mobility and can help to better understand the effect of Mn in enhancing Mn-doped CeO2 catalytic performance in oxidation reactions.